Millennial-scale fluctuations of the European Ice Sheet at the end of the last glacial, and their potential impact on global climate. (1st September 2015) - Toucanne, Samuel; Soulet, Guillaume; Freslon, Nicolas; Silva Jacinto, Ricardo; Dennielou, Bernard; Zaragosi, Sébastien; Eynaud, Frédérique; Bourillet, Jean-François; Bayon, Germain
Abstract: Reconstructing Northern Hemisphere ice-sheet oscillations and meltwater routing to the ocean is important to better understand the mechanisms behind abrupt climate changes. To date, research efforts have mainly focused on the North American (Laurentide) ice-sheets (LIS), leaving the potential role of the European Ice Sheet (EIS), and of the Scandinavian ice-sheet (SIS) in particular, largely unexplored. Using neodymium isotopes in detrital sediments deposited off the Channel River, we provide a continuous and well-dated record for the evolution of the EIS southern margin through the end of the last glacial period and during the deglaciation. Our results reveal that the evolution of EIS margins was accompanied with substantial ice recession (especially of the SIS) and simultaneous release of meltwater to the North Atlantic. These events occurred both in the course of the EIS to its LGM position (i.e., during Heinrich Stadial –HS– 3 and HS2; ∼31–29 ka and ∼26–23 ka, respectively) and during the deglaciation (i.e., at ∼22 ka, ∼20–19 ka and from 18.2 ± 0.2 to 16.7 ± 0.2 ka that corresponds to the first part of HS1). The deglaciation was discontinuous in character, and similar in timing to that of the southern LIS margin, with moderate ice-sheet retreat (from 22.5 ± 0.2 ka in the Baltic lowlands) as soon as the northern summer insolation increase (from ∼23 ka) and an acceleration of the margin retreat thereafter (from ∼20 ka). Importantly, our results show that EIS retreat events and release of meltwater to the North Atlantic during the deglaciation coincide with AMOC destabilisation and interhemispheric climate changes. They thus suggest that the EIS, together with the LIS, could have played a critical role in the climatic reorganization that accompanied the last deglaciation. Finally, our data suggest that meltwater discharges to the North Atlantic produced by large-scale recession of continental parts of Northern Hemisphere ice sheets during HS, could have been a possible source for the oceanic perturbations (i.e., AMOC shutdown) responsible for the marine-based ice stream purge cycle, or so-called HE's, that punctuate the last glacial period. Highlights: Nd isotope evidence for sources of Channel River meltwater discharges. Meltwater discharges caused by recession of the EIS into the North European Plain. Timing of runoff pulses provide new insights into EIS history. Temporal match between runoff pulses and AMOC shutdown reveals the role of the EIS in past global climate changes.